Μελέτη, σχεδιασμός, διαστασιολόγηση και ενεργειακή αξιολόγηση συστήματος ηλιακής θέρμανσης και παράγωγης ζεστού νερού στο νοσοκομείο Κυπερούντας - Γιαννάκη, Παναγιώτης (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
The purpose of this project is the study, design, and energy evaluation of an active solar system for combined heating and domestic hot water at Kyperounda’s Hospital. In the introductory first chapter terms such as thermal comfort, temperature, factors affecting the comfort of the people are explained. After the initial architectural design of the building and on-site visits made in order to diagnose the extent of the work to be done, it was showed that under the existing legislation any renovation work should be followed by the energy upgrading of the building. At this stage, suggestions for the energy upgrade of the Hospital were made and the calculation of the heat load of the building carried out with two parallel processes as followed: a) Calculation of the buildings heat load on the existing condition of the building. b) Calculation of the buildings heat load based on the adoption of measures of energy upgrade. The outcome of the above process was to indicate that the energy upgrade will yield a 62% reduction in heat loss. Next, an introduction to renewable energy sources and solar engineering was made with greater focus on solar energy and the parameters affecting it. Attempts of an overview on the types of solar panels, as well as the thermal characteristics in assembly are made and subsequently there is a first approach of how they could be installed and operated at the Hospital. Then the importance of thermal storage of solar energy was explained and the design parameters for the proper amount of hot water storage were set. After a brief introduction to the types of solar systems there was an explanation of the software program «F-Chart» which was used to determine the optimal number of solar panels. Each parameter was introduced in the software explained, planned or decided and after the "running" of the software, the optimal number of solar panels was determined. The Chapters 6 and 7 followed a computational process of sizing and selecting equipment which the active system consists of. In some cases this process was proved to be time consuming and repetitive and to overcome this problem a computer calculating file was developed. Then a diagrammatic system was designed, which is the way that the equipment of the active solar thermal system is installed or connected. At the end, the final design of the system was cost and the solar thermal system was checked whether the data that was assumed in Chapter 5 and introduced to the software were correct. After the final economic analysis, the investment was assessed and the final conclusions were exported.
Keywords: Active Solar System; Heat Load; Renewable Energy Sources; Σύστημα Συνδυασμένης Θέρμανσης; Θερμικό Φορτίο; Ανανεώσιμες Πήγες Ενέργειας